2013
DOI: 10.1002/hed.23405
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of failure in patients with adenoid cystic carcinoma of the head and neck. An international collaborative study

Abstract: The clinical course of ACC is slow but persistent. Paranasal sinus origin is associated with the lowest distant metastases rate but with the poorest outcome. These prognostic estimates should be considered when tailoring treatment for patients with ACC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
50
2
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 27 publications
3
50
2
3
Order By: Relevance
“…ACC cells in LN may extend to the membrane structure with a result of adjacent soft tissue involvement. In the study of Amit et al (2014b), LN extracapsular spread was statistically correlated with DM rate in univariate analysis but not in multivariate analysis, which was in accordance with our findings concerning DM rate.…”
Section: Discussionsupporting
confidence: 95%
See 3 more Smart Citations
“…ACC cells in LN may extend to the membrane structure with a result of adjacent soft tissue involvement. In the study of Amit et al (2014b), LN extracapsular spread was statistically correlated with DM rate in univariate analysis but not in multivariate analysis, which was in accordance with our findings concerning DM rate.…”
Section: Discussionsupporting
confidence: 95%
“…However, this rate was higher than the local recurrence ratio of 3.3% in the study of early stage ACC of the major salivary gland (Bhayani et al, 2012). The overall DM rate was 36.1% in our patients with predominant site of lung, and it was much higher than the average incidence of about 15%e20% as demonstrated by previous works (Li et al, 2011;Agarwal et al, 2008;Van et al, 2013;Amit et al, 2014b;Bianchi et al, 2008;Maciejewski et al, 2002). ACC patients with LN involvement had higher DM rates (40%) than those without LN invasion (27%) (Amit et al, 2014a).…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…Hence, it is classified as ''high risk'' by the World Health Organization [10]. The overall survival of the present study was approximately the same as, much better or less than those reported in the other studies [7,[11][12][13][14]. The differences between their data and the present study were evaluated in terms of the following: (1) the outcome for patients with ACC is site dependent [15].…”
Section: Discussionmentioning
confidence: 60%